Collective Excitation of Kr-82 - J.K.Jabber; A.A.Mohammed-Ali; A.M.Al-Jumaily (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
The energy level scheme of 82 Kr has been established On the basis of singles gamma spectra, gamma coincidence and Compton suppression measurements. Ge (Li) detectors were used to study the gamma spectra produced in the B- decay of Br to 82 Kr. A total of thirty-six -rays were observed. of which two at 182.9" and 454.98 kev are new. These two transitions considered are to depopulate new 5) level at 3001-31 keV Relative intensities and 10g ft values were calculated and spin / parities deduced